Effectiveness of Information Technology (IT) Classroom Learning on Motivation dan Careers Students of Junior High School - Siti Sundari; Muchlas Muchlas; Muhammad Sayuti (Journal of Vocational Education Studies, 2022)
The purpose of this research is to analyze the level of effectiveness of the information technology-based learning process for increasing students' learning motivation and careers at SMP Muhammadiyah 2 Cilacap and to analyze the differences in the results of the learning process between information technology classes and regular classes. The research activity was carried out using a quantitative descriptive method with a total of 76 subjects. Data collection related to the above objectives used a questionnaire. The data that has been collected is then analyzed using a real difference test, namely the independent sample t-test. The results showed an increase in the effectiveness of the learning process and the growth of learning motivation in students. However, about careers and insight into students' careers. The results showed that the insight into the careers of the students of SMP Muhammadiyah 2 Cilacap was not optimal. Then the learning outcomes shown also experienced differences between the information technology class and the regular class.